Tuberculosis in Healthcare Workers: A Matched Cohort Study in Taiwan. - Sung-Ching Pan; Yee-Chun Chen; Jann-Yuan Wang; Wang-Huei Sheng; Hsien-Ho Lin; Chi-Tai Fang; Shan-Chwen Chang (PLoS ONE, 2015)
Background Proportional mortality ratio data indicate that healthcare workers (HCWs) have an elevated tuberculosis (TB) mortality. Whether this is caused by an increased TB incidence, a worse TB treatment outcome, or a combination of effects, remains unclear. To elucidate the hazard components of occupational TB, we assessed TB incidence and TB treatment outcome among HCWs in Taiwan. Methods We compared the incidence of active TB among HCWs at a major medical center in Taiwan with that of Taiwan general population in 2004-2012. We also compared the TB treatment outcome of HCWs with that of age/sex-matched non-HCW patients treated at the same hospital, as well as that of nationally registered TB patients. Results The standardized TB incidence ratio of the HCWs was 1.9 (95% confidence interval [CI]: 1.2-2.9), compared with the general population. HCWs with pulmonary TB (n = 30) were less likely to have underlying diseases, delay in diagnosis, delay in treatment, or side effects of treatment, compared with age/sex-matched non-HCW TB patients (n = 120) (all Ps<0.05). The TB treatment outcome of HCWs was significantly better than that of non-HCW patients (TB-related mortality: 0.0% vs. 5.8%, P = 0.008, Mantel-Haenszel test). The standardized TB-related mortality rate was 1.08% [95% CI: 0.96% - 1.20%] for all of the nationally registered TB patients in Taiwan. Conclusions HCWs are at increased risk of active TB, compared with general population. To mitigate this occupational hazard, more efforts need to be directed towards the prevention of nosocomial TB transmission. Healthy worker effect, more rapid diagnosis, and less delay in treatment contribute to a lower TB-related mortality in HCWs.